High School Staff Characteristics and Mathematics Test Results - Fetler, Mark (Education Policy Analysis Archives, 1999)
This study investigates the relationship between measures of mathematics teacher skill and student achievement in California high schools. Test scores are analyzed in relation to teacher experience and education and student demographics. The results are consistent with the hypotheses that there is a shortage of qualified mathematics teachers in California and that this shortage is associated with low student scores in mathematics. After controlling for poverty, teacher experience and preparation significantly predict test scores. Short-term strategies to increase the supply of qualified mathematics teachers could include staff development, and recruitment incentives. A long-term strategy addressing root causes of the shortage requires more emphasis on mathematics in high school and undergraduate programs.